Impact of income on life expectancy: A challenge for the pension policy - Damian Walczak; Jacek Wantoch-Rekowski; Robert Marczak (Risks, 2021)
The aim of this paper is to present life expectancy of both genders depending on their income and to determine the impact of a possible regularity on the state pension policy. The study was based on the income of pensioners in Poland (over 5 million people receiving old-age pension). The results obtained made it possible to formulate several important conclusions: the rich live longer; the impact of income on life expectancy is much stronger among men than women; and with age, income has less and less impact on life expectancy. Consequently, in the capital model that is in force in Poland, the state should take this fact into account in its pension policy when calculating the amount of the benefit.
Keywords: 330; gender gap; life expectancy; mortality; pension policy; welfare justice